(untitled) (FAVE Sección Ciencias Veterinarias, 2018)
The resistance of a population of Rhipicephalus microplus (Acari: Ixodidae) to fipronil 1% (ECTOLINE®) in the east of Santiago del Estero, Argentina, is described in this work. The trials were performed as replicates in two establishments: “Establishment A” and “Establishment B”. The differences in the level of tick infestation between treated and control groups in the Establishment A were not significant. The efficacy percentage ranged from 27.3% to 69.3%. Contrarily, the differences between treated and control groups in the Establishment B were significant, with efficacy percentage increasing from 87.6% (day 2 post-treatment) to 95.4% (day 7 post-treatment). The eclosion rates of the eggs produced by the engorged females collected in both treated and control groups in Establishment A were similar. The application of fipronil 1% in the Establishment B had an efficacy almost absolute, because even though the therapeutic efficacy did not reach 100%, the reproductive viability of the engorged females collected on the treated cattle was null. The results of this work constitute the first published record of a population of R. microplus resistant to fipronil 1% under field conditions in Argentina.